Effectiveness of Tactical Games Approach in Badminton Learning: A Systematic Review on Motor Skill Development in Physical Education - Andi Yulianti Basith; Ichsani Ichsani (ILIN Education Indonesia, 2026)
The Tactical Games Approach (TGA) has emerged as a prominent instructional framework in physical education, particularly in the context of game-based sports such as badminton. This systematic review examined the effectiveness of TGA in developing motor skills among students in physical education settings. A comprehensive literature search was conducted across multiple electronic databases, including Scopus, Web of Science, ERIC, and Google Scholar, covering publications from 2020 to 2024. A total of 28 studies met the inclusion criteria and were subjected to thematic analysis. The findings revealed that TGA significantly enhanced students' motor skill acquisition in badminton, encompassing both technical execution and tactical decision-making. Furthermore, TGA was found to foster greater student engagement, intrinsic motivation, and transfer of learning compared to traditional drill-based instruction. Contextual factors such as class size, instructional duration, and teacher pedagogical competence were identified as moderating variables. The review concludes that TGA represents a pedagogically sound and evidence-based approach to badminton instruction in physical education, with implications for curriculum design and teacher professional development